Exploring the Integration Between Colour Theory and Biodiversity Values in the Design of Living Walls - Thorpert, Petra; Rayner, John; Haaland, Christine; Englund, Jan-Eric; Fransson, Ann-Mari (Frontiers in Ecology and Evolution, 2022)
Designing green infrastructure in cities requires vegetation that has multiple outcomes and functions, particularly using plants that have both attractive visual or aesthetic features and high biodiversity values. Plantings that have high visual appeal are more highly valued by people and increase their feeling of well-being. Increasing biodiversity in cities is one of the major challenges facing urban planning and design. However, balancing biodiversity and aesthetic outcomes in urban planting design is complex, and to date there are few methods that can be used to guide plant selection. To address this knowledge gap, we investigated the use of a colour theory framework for planting arrangements to see if we could design vegetation that is highly aesthetic and has high biodiversity. We did this by configuring planting combinations for living walls in Malmö, Sweden, using principles based on Johannes Itten's colour theories. The plant combinations on each wall were graphically arranged using 1) colour analysis of each plant and 2) design of the plant species into two colour schemes: light-dark colour concept and a complementary colour concept. For each species used in the compositions we created a biodiversity classification, based on its pollination value, ‘nativeness’ and conservation value as a cultivar; and a plant visual quality classification, based on the performance from living walls studies. The graphical colour composition and interlinked biodiversity value were then compared to designs created with randomly selected plant species. The results showed that it is possible to design a living wall based on colour theory without compromising with biodiversity outcomes, namely species richness, pollination and the nativeness of the species. The results also indicate the potential application of this design approach to deliver greater aesthetic appreciation and enjoyment from plantings. While more work is needed, this study has shown that a theoretical colour framework can be a useful tool in designing green infrastructure to improve delivery of both cultural and regulatory ecosystem services.